Intimate partner violence and repeat induced abortion in Italy: A cross sectional study. (3rd September 2015) - Citernesi, Angela; Dubini, Valeria; Uglietti, Anna; Ricci, Elena; Cipriani, Sonia; Parazzini, Fabio
Abstract: Objective To investigate the impact of intimate partner violence (IPV) on the risk of repeat induced abortion (RIA), we compared IPV history among women with and without previous induced abortion (IA). Methods All consecutive women aged 18 years or more requiring IA in 12 Italian abortion clinics were eligible for inclusion in the study. They were asked to fill in an anonymous, self-developed questionnaire assessing sociodemographic data and their history of different types of violence and related risk factors. Results The analysis included 1030 women, 624 (60.6%) of whom reported a previous IA. Past or current IPV was reported by 19.3%: 7.0% reported sexual violence, 11.3% physical abuse and 12.1% psychological abuse. Past or current IPV was reported by 22.3% of women with RIA and 14.8% of those undergoing their first IA (adjusted odds ratio 1.57, 95% confidence interval 1.07–2.30; p = 0.02). When we considered sexual, psychological and physical abuse separately, we found that any kind of abuse was more frequent in women with RIA than in women with no previous IA. Conclusion This study underlines the impact of IPV on the risk of RIA and suggests the need for screening for IPV among women requiring abortion, in order to identify women at risk of RIA and to improve their general and reproductive health. Chinese Abstract 摘要： 目的： 为了研究亲密伴侣暴力对反复人工流产的影响，我们比较了既往有亲密伴侣暴力病人有无反复流产史。 方法： 在意大利12所堕胎诊所需要行人工流产术的所有的18周岁及以上的妇女符合此研究的纳入标准，她们需要填写一份匿名的、自主研发的问卷，调查研究社会人口数据和既往的暴力性质及与此相关的影响因素。 结果： 共有1030人纳入研究，其中的624（60.6%）既往有过人工流产史。目前的研究表明亲密伴侣暴力的发生率为19.3%，其中7.0%为性暴力，11.3%躯体虐待，12.1%为心理暴力。目前的研究提出，既往有过人工流产史的妇女中发生亲密伴侣暴力的概率是22.3%，第一次行人工流产的妇女中亲密伴侣暴力的发生率是14.8%（调整后OR=1.57, 95%CI 1.07-2.30, P=0.02）。当我们将性、躯体、心理的虐待分开来考虑，发现不同形式的虐待在既往有人工流产史的妇女中的发生频率均高于在初次行人工流产的妇女的发生频率。 结论： 这项研究强调了亲密伴侣暴力对反复人工流产的影响，建议在妇女需要行人工流产时调查有无亲密伴侣暴力的存在，从而识别有无反复人工流产的危险因素，并提高妇女的健康及生殖健康。 关键词： 亲密伴侣暴力，人工流产， 流行病学，危险因素，性虐待